2016
DOI: 10.1021/acs.est.6b03567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biodiesel Fuels on Real-World Emissions of Passenger Locomotives

Abstract: Few data are available regarding the effect of biodiesel on exhaust emission rates of two-stroke engines used in many passenger locomotives. Using a portable emissions measurement system (PEMS), duty cycle average nitrogen oxides (NO), hydrocarbons (HC), carbon monoxide (CO), particulate matter (PM), and carbon dioxide (CO) emission rates were measured for three locomotives operating on ultra-low sulfur diesel (ULSD) and soy-based B10, B20, and B40 biodiesel blends. Measurements were conducted in the rail yard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…Combustion of both diesel and biodiesel results in the generation of toxic gases and respiratory irritants such as carbon dioxide, carbon monoxide, nitrogen oxides and sulfur dioxide . The results of previous studies comparing the gaseous outputs of the two exhausts vary considerably 4,9,33,34 . The majority have found that biodiesel exhaust contains more NOx as well as a decrease in the average size of the particulate matter 4,7,8 and this study has found similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Combustion of both diesel and biodiesel results in the generation of toxic gases and respiratory irritants such as carbon dioxide, carbon monoxide, nitrogen oxides and sulfur dioxide . The results of previous studies comparing the gaseous outputs of the two exhausts vary considerably 4,9,33,34 . The majority have found that biodiesel exhaust contains more NOx as well as a decrease in the average size of the particulate matter 4,7,8 and this study has found similar results.…”
Section: Discussionmentioning
confidence: 99%
“…The SEMTECH-DS measures NO, NO 2 , and NO x concentrations based on the same detection methods as specified in 40 CFR 1065 Subpart J . The bias correction factor for each throttle notch position of each locomotive was estimated as the ratio of notch-average NO x /NO concentrations measured using a SEMTECH-DS PEMS. ,,, For several heavy-duty diesel engines, the laser light scattering-based PM concentrations were correlated with the FRM. The slope of linear regression of FRM versus laser light scattering was reported as 5. Thus, laser light scattering is typically biased low by a factor of 5.…”
Section: Methodsmentioning
confidence: 99%
“…Exhaust concentrations and engine activity data were recorded every second. Details of the installation are described elsewhere ( 8 10 ).…”
Section: Methodsmentioning
confidence: 99%
“…To quantify energy consumption of individual trips, field measurements or model simulations can be used ( 7 ). Field measurements have been conducted using a portable emission measurement system (PEMS) for diesel-electric locomotives ( 8 , 9 ). Field measurements using PEMS provide comparable results to federal reference methods (FRMs) based on engine dynamometer measurements ( 10 ).…”
mentioning
confidence: 99%